Neutrophils Promote Tumor Progression in Oral Squamous Cell Carcinoma by Regulating EMT and JAK2/STAT3 Signaling Through Chemerin - Hu, Xiaoyuan; Xiang, Fenggang; Feng, Yuanyong; Gao, Fei; Ge, Shengyou; Wang, Chengqin; Zhang, Xuan; Wang, Ning (Frontiers in Oncology, 2022)
Oral squamous cell carcinoma (OSCC) is the most common malignancy of the oral cavity. In the tumor microenvironment, tumor-associated neutrophils (TANs) can promote tumor growth, invasion, and metastasis. The aim of our study was to explore the relationship between neutrophils infiltration and Chemerin expression in tumor cells, as well as their relationship with the clinicopathological parameters and clinical prognosis of 74 cases of OSCC. We also explored the role of the interaction between neutrophils and Chemerin in the functions of OSCC cells (Cal27, SCC9, and SCC15) in vitro. Our results showed that in OSCC, Chemerin over-expression may increase neutrophils infiltration in tumor tissues. Chemerin over-expression and neutrophils infiltration were the prognostic factors of poor clinical outcomes. Furthermore, we discovered that neutrophils promoted OSCC migration, invasion, and proliferation and EMT through Chemerin. Neutrophils activated JAK2/STAT3 signaling through Chemerin and then up-regulated its downstream signaling target genes, such as Phospho-Rb, E2F1, CyclinE1, and CyclinD1. Taken together, our results revealed that neutrophils and Chemerin are potentially involved in OSCC progression and metastasis. Neutrophils may promote the JAK2/STAT3 signaling pathway and EMT in OSCC cells through Chemerin.